The Leadership Strategy of The School Principal in Improving Teachers’ Performance in SMA Muhammadiyah 4 Surabaya - Siti Mariyati; Zainuddin Maliki (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
the senior high school of Muhammadiyah 4 Surabaya is a school continually experienced various developments including in an effort to improve the performance of the teachers. SMA Muhammadiyah 4 Surabaya is a religion-based school in Karangpilang which experiences increasing number of students and community interest from year to year. It cannot be separated from the strategy and active role of the principal. This study aims to find out and explore what is the leadership strategy of school principals in improving teachers’ performance in SMA Muhammadiyah 4 Surabaya? And what are the supporting factors and obstacles of school principals in improving teachers’ performance in SMA Muhammadiyah 4 Surabaya? This is a qualitative research with descriptive approach. The process of data collection is done by using observation, interview and documentation. Data are collected and analyzed through several stages including data collection, reduction, and presentation then drawing conclusions in accordance with the scope of the problem. As the findings of this study, it can be concluded that: First, Principal Leadership Strategy in improving teacher performance in SMA Muhammadiyah 4 Surabaya consists of 9 strategies. Second, the supporting factors in this school environment consist of 3 factors and the inhibiting factors consist of 2 factors. The supporting factors are teacher education level, conducive climate, and mental condition of the teachers. The inhibiting factors are caused by internal and external factors. The internal factor is budget limitation while the external factor is the parents’ financial conditions. Keywords: Strategy, Leadership, Teachers’ Performance